2015
DOI: 10.1080/08997659.2014.983278
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Egg Ozonation on Hatching Success, Larval Growth, and Survival of Atlantic Cod, Atlantic Salmon, and Rainbow Trout

Abstract: The direct exposure of fish eggs to ozonated water has generated interest as a means of ensuring pathogen-free eggs without the use of harsh chemicals. However, there are numerous knowledge gaps, including safe contact times, exposure levels, and potential long-term effects on aquaculture species in both freshwater and seawater. The effect of different ozone (O3) doses (0.5-1.0, 1.5-2.0, and 2.5-3.0 mg of O3/L for 90 s) on recently fertilized eggs of Atlantic Cod Gadus morhua and eyed eggs of Atlantic Salmon S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
3
1
0
Order By: Relevance
“…The degree of ozone penetration across egg shells was not correlated with gas concentration in the environment. This is in agreement with previous reports indicating that there are a high number of pores on the egg shell blunt end just above the air cell (Fry et al 2015). Braun et al (2011), have investigated the feasibility of gaseous ozone to reduce the number of microorganisms on the shell surface, of Salmonella enteritidis (S.e) in particular, of avian hatching eggs.…”
Section: Resultssupporting
confidence: 91%
“…The degree of ozone penetration across egg shells was not correlated with gas concentration in the environment. This is in agreement with previous reports indicating that there are a high number of pores on the egg shell blunt end just above the air cell (Fry et al 2015). Braun et al (2011), have investigated the feasibility of gaseous ozone to reduce the number of microorganisms on the shell surface, of Salmonella enteritidis (S.e) in particular, of avian hatching eggs.…”
Section: Resultssupporting
confidence: 91%
“…Such delays or decreases have been reported as side effects of ozonation in some marine fish species, such as Latris lineata (BATTAGLENE;MOREHEAD 2006). On the other hand, as demonstrated in zebrafish here, Oncorhynchus mykiss and Hippoglossus hippoglossus embryos have shown satisfactory hatching and growth results in ozonated water (FRY et al, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…Hao et al (2015) determined that the safe concentration of ozonated water for zebrafish embryos was 0.1 mg/L and reported that this concentration allowed survival and did not harm the animals. Resistance to ozonation was also found by other authors in embryos of marine fish such as Gadus morhua and Hippoglossus hippoglossus, being 3 mg/L and 2 mg/L respectively (FRY et al, 2015;GROTMOL et al, 2003). The embryos of the marine fish species Hippoglossus hippoglossus showed greater sensitivity to ozonation (GROTMOL et al, 2003).…”
Section: Discussionsupporting
confidence: 61%
“…In Fry et al. (), four treatments (ozone at low, standard and high concentrations, and Perosan) exhibited no effect on the yolk sac conversion efficiency of rainbow trout Oncorhynchus mykiss larvae of DAH 0–30. As discussed above, these effects are usually species, disinfection agent and concentration specific.…”
Section: Discussionmentioning
confidence: 96%